Analisis Variansi sebagai Pengendali Biaya dengan Menggunakan Metode Biaya Standar: Esti Wahyuningsih*, Saradiva Diani S, Elyan Adistia, Amelia Putri - Esti Wahyuningsih; Saradiva Diani S; Elyan Adistia; Amelia Putri (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2024)
This research was conducted to determine the results of analysis of variance of production costs. The Sido Mampir restaurant business is engaged in the culinary business. Proper analysis of variance will help the company determine its selling price. Determining the right selling price will of course have an impact on achieving the profit desired by the company. The production costs analyzed are raw material costs and labor costs using the standard cost method. Standard costing is based on previous period data and environmental conditions. Variance analysis is carried out so that calculations are in accordance with accounting standards so that they can become a consideration for owners to use the standard cost method by comparing the standard costs set with the actual costs or actual costs. This study uses a descriptive qualitative approach. Sources of data are primary data and secondary data by visiting the place of business directly. Research techniques are interviews and documentation. The result of the research is that the analysis of variance for raw material costs and labor costs in the Sido Mampir food stall business is favorable, meaning that these costs are used effectively and efficiently in cost control